2013
DOI: 10.1186/1749-8090-8-176
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers for predicting outcomes in CABG cardiothoracic surgeries

Abstract: The variations in recovery time, complications, and survival among cardiac patients who have undergone coronary artery bypass graft (CABG) procedures are vast. Many formulas and theories are used to predict clinical outcome and recovery time, and current prognostic predictions are based on medical and family history, lifestyle, comorbidities, and performance status. The identification of biomarkers that provide concrete evidence supporting clinical outcome has greatly affected the field of medicine, helping cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…Previous studies also found the same results (21)(22)(23)(24). Some researchers also reported increased sodium levels after liver transplant is associated with postoperative complications (13)(14)(15)(16)(25)(26)(27)(28)(29). However another study found this correlation with lower mortality and complications (30).…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies also found the same results (21)(22)(23)(24). Some researchers also reported increased sodium levels after liver transplant is associated with postoperative complications (13)(14)(15)(16)(25)(26)(27)(28)(29). However another study found this correlation with lower mortality and complications (30).…”
Section: Discussionsupporting
confidence: 57%
“…Coronary artery disease is the leading cause of death globally and can be treated by coronary artery bypass grafting (CABG). Exposure of patient blood to the bypass circuitry and re‐perfusion following CABG is associated with activation of leucocytes, complement and cytokine secretion . Activation of the patient’s inflammatory response following CABG has been suggested to contribute to, and be a potential indicator of adverse outcomes including infection, increased ICU length of stay (LOS), atrial fibrillation (AF), myocardial infarction, respiratory distress, multiple organ dysfunction (MOD), acute kidney injury and mortality …”
Section: Introductionmentioning
confidence: 99%
“…However if these methods were not responsive, to resolve problems coronary artery bypass graft surgery is done (CABG) in order to increase survival and improve the quality of patients' lives (1,2). There are some early postoperative complications including peri-operative myocardial infraction in CABG in spite of its favorable long term outcome.…”
Section: Introductionmentioning
confidence: 99%